A systematic review of the influence of technology-mediated employment interview on applicant reactions from 2000-2010 - Mohd. Taib, Maisarah; Alias, Alizi (2010)
In this technology savvy world, the use of technology has become a common practice in organization even for personnel selection purpose. Among tools of selection that has begun utilising technologies for its medium is the employment interview which is most profound among the researchers as technology-mediated employment interview. The present study presents a systematic review of recent research on technology-mediated employment interview (i.e., interactive voice response interview, IVR; telephone interview, TI; videoconference interview, VI) in personnel selection with particular preference to applicant reactions. Via computer-assisted searches of social science databases, gateways, publications from relevant organizations, hand searched key journals and scanned reference lists, a total of five studies (3 experimental studies; 2 non-experimental studies) were selected and critically appraised. All studies demonstrated a mixed result. Three experimental studies found consistent results of negative applicant reactions on VI, but for TI, one study demonstrated positive applicant reactions while another study showed negative applicant reactions. With non-experimental studies, compared to VI and IVR, TI received consistent positive applicant reactions. All five studies had significant methodological flaws, particularly the absence of power calculations across all studies. With the insufficient, contradictory and methodologically flawed evidence, the present study noted several important key messages and further depict a hypothetical research model to guide future research in this area.